Training on synthetic ethylene-vinyl acetate bench model allows novice medical students to acquire suture skills - Denadai, Rafael; Saad-Hossne, Rogerio [UNESP]; Oshiiwa, Marie; Bastos, Erika Malheiros (Acta Cirúrgica Brasileira, 2012)
PURPOSE: To assess the acquisition of suture skills by training on ethylene-vinyl acetate bench model in novice medical students.METHODS: Sixteen medical students without previous surgery experience (novices) were randomly divided into two groups. During one hour group A trained sutures on ethylene-vinyl acetate (EVA) bench model with feedback of instructors, while group B (control) received a faculty-directed training based on books and instructional videos. All students underwent a both pre-and post-tests to perform two-and three-dimensional sutures on ox tongue. All recorded performances were evaluated by two blinded evaluators, using the Global Rating Scale.RESULTS: Although both groups have had a better performance (p<0.05) in the post-test when compared with the pre-test, the analysis of post-test showed that group A (EVA) had a better performance (p<0.05) when compared with group B (control).CONCLUSION: The ethylene vinyl acetate bench model allowed the novice students to acquire suture skills faster when compared to the traditional model of teaching.

OBJETIVO: Avaliar a aquisição das habilidades de sutura com o treinamento no modelo de bancada de etileno vinil acetato em acadêmicos de medicina. MÉTODOS: Dezesseis estudantes de medicina iniciantes na prática cirúrgica foram divididos aleatoriamente em dois grupos. Durante uma hora o grupo A treinou diferentes suturas no modelo de bancada de etileno vinil acetato (EVA) com feedback dos instrutores, enquanto os do grupo B (controle) receberam um treinamento dirigido por instrutor baseado em livros e vídeos didáticos. Todos foram submetidos à pré e pós-testes para realização de suturas bi e tridimensionais em língua de boi. As performances gravadas foram avaliadas por dois avaliadores cegos, utilizando a Global Rating Scale. RESULTADOS: Embora os dois grupos tenham apresentado um melhor desempenho (p<0.05) no pós-teste quando comparado com o pré-teste, a análise do pós-teste mostrou que os alunos do grupo A (EVA) tiveram um melhor desempenho (p<0.05) quando comparados com os do grupo B (controle). CONCLUSÃO: O modelo de etileno vinil acetato permitiu que os alunos adquirissem habilidades de sutura mais rapidamente quando comparado ao modelo tradicional de ensino.
Treinamento no modelo de bancada sintético de etileno vinil acetato permite que estudantes de medicina iniciantes na prática cirúrgica adquiram habilidades de sutura
Keywords: Education, Medical; Surgery; Sutures; Teaching; Teaching Materials